Pyrolysis of eastern redcedar: Distribution and characteristics of fast and slow pyrolysis products. (15th February 2016) - Yang, Zixu; Kumar, Ajay; Huhnke, Raymond L.; Buser, Michael; Capareda, Sergio
Highlights: Wood zone (heartwood and sapwood) effects bio-oil composition. Cedar wood oil yield (α/β-cedrene) can be maximized through slow pyrolysis. Heartwood produced significantly more α/β-cedrene than sapwood. Slow pyrolysis yielded small molecules derived from primary pyrolysis products. Abstract: Eastern redcedar is a problematic plant in Oklahoma due to its extinguished environmental flexibility and rapid expansion. Thermally converting solid biomass polymers into liquid fuel intermediate, solid char and gaseous products through pyrolysis is one promising approach to use redcedar for the production of sustainable fuels. The objective of this study was to investigate effects of eastern redcedar wood zones (heartwood and sapwood), pyrolysis temperature (450 and 500 °C) and pyrolysis types (slow at lab-scale and fast at micro-scale) on the distribution and composition of the pyrolysis products. In fast pyrolysis conditions, the products were dominated by anhydrous sugars, phenols and guaiacols. The total yield of lignin-derived compounds from heartwood was higher than that from sapwood at 500 °C but the total yields were not significantly different at 450 °C. In slow pyrolysis conditions, acetic acid and furfural were the two most abundant species in bio-oil. Slow pyrolysis products consisted of less branched compounds of phenols and guaiacols as compared to fast pyrolysis products. Cedar oil components (alpha/beta-cedrene) were only produced at slow pyrolysis conditions and its maximum yield (21.04 ± 1.08 area%) of was obtained from heartwood at 500 °C. Heartwood produced significantly more cedrenes than sapwood.